Simulatorji: opis učnih vsebin: gradivo za študente, 1. zvezek - Skalicky, Marjan (University of Maribor Press, 2019)
Simulations: Teaching Content: Student Material, Volume 1. At the Maribor hospital, the clinical use of ultrasound (US) was introduced in 1968. This year, we are marking the 50th anniversary of regular diagnostic and interventional ultrasound training. Students at the Faculty of Medicine of the University of Maribor have been learning how to use ultrasound since 2004. They welcomed this program knowing that today every physician shall be equipped with a portable US. The training is delivered as regular curricula and as a selective subject using simulators so that students can practice on each other and on themselves. During their 6th year and under the supervision of a mentor, students complete the introduction into clinical work also referred to as propaedeutics. Equipment owned by the Faculty of Medicine is available at the divisions of the University Medical Centre Maribor. Furthermore, this paper discusses simulation trainings for human physiology and pathophysiology, medical emergencies, resuscitation guidelines, upper and lower gastrointestinal endoscopy, vaginal and surgical birth, and a training simulator for both basic and advanced laparoscopic procedures. The simulators include programs for a range of higher-level competencies and thus intended for the use of postgraduate medical studies.